Rethinking European welfare : transformations of Europe and social policy - Fink, Janet; Lewis, Gail, 1951-; Clarke, John, 1950-; Open University (London : SAGE, 2001)
Comprises twelve essays which explore ways of thinking about the relationships between Europe and social policy. Highlights the link between social policy and the formation of social solidarities and identifications of belonging. Demonstrates the difficulties in defining the territorial, political and cultural boundaries within Europe, addressing methodological issues in comparative social policy analysis, and explores the construction of social differences and identities and particular areas of welfare policies.
Introduction: Transitions and trajectories in European welfare / Gail Lewis, Janet Fink, and John Clarke -- PART ONE: UNSETTLING BOUNDARIES AND BORDERS: Introduction -- Re-shaping Europe: the challenge of new divisions within a homogenized political-economic space / Roy Hudson and Allan M. Williams -- Changing citizenship in Europe: remarks on postnational membership and the national state / Yasemin N. Soysal -- Europe's civilising mission / Phil Marfleet -- Migrant women and exclusion in Europe / Eleonore Kofman and Rosemary Sales -- Conclusion to Part One -- PART TWO: UNSETTING CATEGORIES AND METHODS: Introduction -- Gendering dimensions of welfare states / Diane Sainsbury -- Race/ethnicity, gender, and class in welfare states: a framework for comparative analysis / Fiona Williams -- Silence, absence and elision in analyses of 'the family' in European social policy / Janet Fink -- Cultural analysis of the informal sphere / Prue Chamberlayne -- Conclusion to Part Two -- PART THREE: UNSETTLING SPACE, PLACE, AND LOCALITY: Introduction -- Re-framing Europe: gendered racisms, ethnicities and nationalisms in contemporary western Europe / Avtar Brah -- Boundaries of social exclusion in Europe / Lila Leontidou and Alex Afouxenidis -- The restructuring of the European educational space: changing relationships among states, citizens, and educational communities / Antonio Novoa -- Drugs, drug culture, and European governance / Eugene McLaughlin and Karim Murji -- Conclusion to Part Three.
Includes bibliographical references and index.
committed to retain
Keywords: x; Public welfare -- Europe; Aufsatzsammlung; Aufsatzsammlung; Aufsatzsammlung; map; 2; mapa